2017
DOI: 10.14309/crj.2017.63
|View full text |Cite
|
Sign up to set email alerts
|

Intussusception after Routine Colonoscopy: A Rare Complication

Abstract: We present a 31-year-old woman who developed ascending colon intussusception several hours after a routine colonoscopy where random mucosal biopsies were obtained. She underwent an ileocolic resection, and pathology did not show an etiology for the intussusception. Colonic intussusception occuring without pathology and after minimal intervention is rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Tafner et al (17) reported that 20 of 30 pediatric intussusception patients could be safely reduced by colonoscopy, and this method is safe because it is non-invasive and the intestine can be directly observed. On the other hand, it has been reported that intestinal intussusception develops iatrogenically after TCS, and further investigation is required for the reduction in intussusception on TCS (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Tafner et al (17) reported that 20 of 30 pediatric intussusception patients could be safely reduced by colonoscopy, and this method is safe because it is non-invasive and the intestine can be directly observed. On the other hand, it has been reported that intestinal intussusception develops iatrogenically after TCS, and further investigation is required for the reduction in intussusception on TCS (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Only 5 cases of post colonoscopy intussusception have been reported in the literature. Two of these patients had polyp removal as part of the screening protocol/colonoscopy [4,7], two presented with diarrhea and normal colonoscopy findings [5], and the last had chronic constipation and pain in the setting of a prior history of low anterior resection for endometriosis [8]. All of them presented with abdominal pain shortly after colonoscopy and CT findings revealed intussusception.…”
Section: Discussionmentioning
confidence: 99%
“…The literature review revealed that only 8 cases, including the present case, have been reported to date. The first case was reported in 2000 by Yamazaki et al; other cases are mentioned in Table 1 [6-12]. The age of presentation ranged from 19 to 73 years, with a male predominance of 5:2.…”
Section: Discussionmentioning
confidence: 99%